2002
DOI: 10.1002/ijc.10608
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐transporting P‐type adenosine triphosphatase (ATP7B) as a cisplatin based chemoresistance marker in ovarian carcinoma: Comparative analysis with expression of MDR1, MRP1, MRP2, LRP and BCRP

Abstract: Intrinsic or acquired resistance to chemotherapy is the major obstacle to overcome in the treatment of patients with solid carcinoma. Cisplatin is one of the most effective chemotherapeutic agents for treating ovarian carcinoma. Recently, copper-transporting P-type adenosine triphosphatase (ATP7B) has been demonstrated as one of the genes responsible for cisplatin resistance in vitro. We hypothesized that the expression of ATP7B gene increases resistance to cisplatin in ovarian carcinoma and a priori knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
63
1
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(89 citation statements)
references
References 33 publications
22
63
1
3
Order By: Relevance
“…These proteins are upregulated in cisplatin-resistant cancer cell lines , and their transfection-enforced overexpression has been shown to drive the acquisition of the cisplatin-resistant phenotype . Importantly, clinical studies indicate that ATP7B expression levels might predict the sensitivity of ovarian and endometrial cancers to cisplatin chemotherapy (Nakayama et al, 2002(Nakayama et al, , 2004Aida et al, 2005). Still, in line with the multifactorial nature of cisplatin efflux (and resistance; see below), small molecules that inhibit specific ABC transporters (for example, the P-glycoprotein-specific inhibitor 5-bromotetrandrine) appear to be unable per se to restore cisplatin accumulation and sensitivity (Jin et al, 2005).…”
Section: Mechanisms Of Pre-target Resistancesupporting
confidence: 39%
“…These proteins are upregulated in cisplatin-resistant cancer cell lines , and their transfection-enforced overexpression has been shown to drive the acquisition of the cisplatin-resistant phenotype . Importantly, clinical studies indicate that ATP7B expression levels might predict the sensitivity of ovarian and endometrial cancers to cisplatin chemotherapy (Nakayama et al, 2002(Nakayama et al, , 2004Aida et al, 2005). Still, in line with the multifactorial nature of cisplatin efflux (and resistance; see below), small molecules that inhibit specific ABC transporters (for example, the P-glycoprotein-specific inhibitor 5-bromotetrandrine) appear to be unable per se to restore cisplatin accumulation and sensitivity (Jin et al, 2005).…”
Section: Mechanisms Of Pre-target Resistancesupporting
confidence: 39%
“…We have extensively studied mechanisms involved in cisplatin resistance (1,2). Several mechanisms are involved in the acquisition of cisplatin resistance (3), which include reduced drug accumulation (4,5), increased production of cellular thiol (6,7) and augmented DNA repair activity (8,9). We have recently reported that two histone acetyltransferases (HAT), Clock and Tip60, are overexpressed in cisplatin-resistant cells (10,11).…”
Section: Introductionsupporting
confidence: 42%
“…More convincing has been the demonstration that human tumor cells transfected with ATP7B acquire significant resistance to both cisplatin (ninefold) and copper (twofold), primarily as a consequence of enhanced cisplatin efflux. The recent proposal to use overexpression of ATP7B as a clinical marker of chemoresistance to cisplatin in ovarian cancer affirms the potentially significant role of the copper transporter in cisplatin resistance (Nakayama et al, 2002).…”
Section: Reduced Intracellular Drug Accumulationmentioning
confidence: 40%